A novel energy-water nexus based CHP operation optimization model under water shortage. (15th January 2022) - Wang, Shuhang; Wang, Xu; Fu, Zhenghui; Liu, Feng; Xu, Ye; Li, Wei
Abstract: A combined heating and power (CHP) system is a distributed energy system with the high energy efficiency and low pollutant emissions. CHP system was capable of supplying the electricity and heat to the users simultaneously and thus was widely applied in the industrial field. However, a large amount of water was exhausted during energy supply process in order to realize the temperature drop of system equipment and steam generation of waste heat boiler. Under the context of global water shortage crisis, the exploration in the relationship between the energy production and water consumption in CHP system was critical, with the aim of reducing water consumption amounts while meeting the user demand and maximizing system benefit as possible. This study selected the CHP system in an industrial park of Jinan City (Shandong Province, China) as the example, where hourly water consumption data of the CHP system throughout the year was available based on the site survey and literature review. The water consumption at each month was fitted firstly and determined to follow a normal distribution. Then, the water-consumption quota under various water guarantee rates was calculated by aid of mean value and variance coefficient. Finally, the relationship between energy supply and water consumption and the maximum water availability were innovatively incorporated into traditional CHP operation optimization model, where a novel energy-water nexus based CHP operation optimization model was formulated. The obtained results demonstrated that with the increase in the guarantee rate, the energy provision of the equipments and total system profit would increase, indicating that the water resource plays an important role in energy generation process. Compared with traditional operation optimization model, energy-water nexus based optimization model realized the balance between water resource protection and energy demand satisfaction and ensured normal operation of CHP system under strict water availability in the future. Graphical abstract: Image 1 Highlights: The normal distribution of monthly water consumption of CHP system was identified. A novel energy-water nexus based CHP operation optimization model was developed. The operation strategies under different water guarantee rates were proposed. The study is expected to alleviate the conflict of energy supply and water reserve.